Synthesis, characterization, and electrochemical, electrical and gas sensing properties of a novel tert-butylcalix[4]arene bridged bis double-decker lutetium(III) phthalocyanine - ÖZKAYA, ALİ RIZA (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
A novel tert-butylcalix[4]arene bridged bis double-decker lutetium(III) phthalocyanine (Lu2Pc4) (5) has been synthesized by the reaction of dimeric lutetium(III) phthalocyanine (4) with two equiv. of dilithium octakis hexylthiophthalocyanine in amyl alcohol. The phthalonitrile derivative 1 was obtained through the displacement reaction of 4-nitrophthalonitrile with 1,3-dimethoxy-4-tert-butyl-calix[4]arene and was converted to the isoindoline derivative 2 by bubbling ammonia gas in dry MeOH. Compound 4 was prepared from 2, 4,5-bis(hexylthio)-1,2-diimilioisoindoline (3), and lutetium acetate in dry DMF. The new compounds and phthalocyanines were characterized by elemental analysis, IR, UV-Vis, H-1 NMR, ESR and MALDI-TOF MS spectra. The electrochemical properties of 4 and 5 have been examined by cyclic voltammetry, and compared. Distinctive differences between the voltammetric behaviour of 4 and 5 were detected. These differences were compatible with the structures of the compounds. A detailed study of the effect of temperature on the d.c. conductivity and impedance spectra (40-10(5) Hz) of spin coated films of 4 and 5 at temperatures between 290 K and 420 K was carried out. By analyzing the d.c. electrical behaviour of the 5 film, it was found that the experimental data are described by a thermally activated conductivity dependence on temperature with an activation energy of 0.77 eV. The a.c. results give a power law behaviour, sigma(a.c.) = A(T)omega(s), in which the frequency exponent s decreases with temperature. The sensing behaviour of the film for the online detection of volatile organic solvent vapors was investigated by utilizing an AT-cut quartz crystal resonator. It was observed that the adsorption of the target molecules on the coating surface cause a reversible negative frequency shift of the resonator. Thus, a variety of solvent vapors can be detected by using the 5 film as sensitive coating, with sensitivity in the ppm and response times in the order of several seconds depending on the dipole moment of the organic solvent. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: phthalocyanine; calix[4]arene; double decker; cyclic voltammetry; gas sensing; LANGMUIR-BLODGETT-FILMS; 16-MEMBERED DIAZADITHIA MACROCYCLES; ACIDIC AQUEOUS-MEDIUM; RARE-EARTH ELEMENTS; THIN-FILMS; ELECTROCHROMIC PROPERTIES; BISPHTHALOCYANINE COMPLEXES; DIPHTHALOCYANINE FILMS; ADSORPTION PROPERTIES; MAGNETIC-PROPERTIES